Pyracantha fortuneana (Maxim.) Li: A comprehensive review of its phytochemistry, pharmacological properties, and product development - Wang, Lingyu; Li, Ruolan; Zhang, Qing; Liu, Jia; Tao, Ting; Zhang, Ting; Wu, Chunjie; Ren, Qiang; Pu, Xufeng; Peng, Wei (Frontiers in Sustainable Food Systems, 2022)
Pyracantha fortuneana (Maxim.) Li has been applicated as an herbal medicine in China for long history. Since ancient times, the fruits of P. fortuneana has been considered a functional food to improve various diseases. Many bioactive substances, including proanthocyanidins, phenols, polysaccharides and dietary fibers, have been isolated and identified from the P. fortuneana, which possess diverse biological properties both in-vitro and in-vivo. Although the researches on the P. fortuneana have achieved extensive progress, the systematic study of its biological activities is still relatively lacking. In addition, accumulating researches focus on the landscape value of the P. fortuneana and the development of its by-products. The by-products of P. fortuneana also show good development potentials in the field of agricultural production and environmental protection, which is important for improving the economic value of P. fortuneana. significance. Reviewing and analyzing the existing published articles, books and patents, this paper aims to systematic summarized the research trends of P. fortuneana and its phytochemical compositions, nutritional values, pharmacological effects and health benefits of its extracts/monomers, wchich would be beneficial for the future development of this medicinal plant as functional food or drugs.